A genome‐wide association study identifies FSHR rs2300441 associated with follicle‐stimulating hormone levels. Issue 6 (30th March 2020) - Yan, Jinting; Tian, Ye; Gao, Xingjian; Cui, Linlin; Ning, Yunna; Cao, Yongzhi; Chen, Yan; Peng, Fuduan; You, Li; Liu, Fan; Zhao, Han
Abstract: Follicle‐stimulating hormone (FSH) and luteinizing hormone (LH) play critical roles in female reproduction, while the underlying genetic basis is poorly understood. Genome‐wide association studies (GWASs) of FSH and LH levels were conducted in 2590 Chinese females including 1882 polycystic ovary syndrome (PCOS) cases and 708 controls. GWAS for FSH level identified multiple variants at FSHR showing genome‐wide significance with the top variant (rs2300441) located in the intron of FSHR . The A allele of rs2300441 led to a reduced level of FSH in the PCOS group ( β = −.43, P = 6.70 × 10 −14 ) as well as in the control group ( β = −.35, P = 6.52 × 10 −4 ). In the combined sample, this association was enhanced after adjusting for the PCOS status (before: β = −.38, P = 1.77 × 10 −13 ; after: β = −.42, P = 3.33 × 10 −16 ), suggesting the genetic effect is independent of the PCOS status. The rs2300441 explained sevenfold higher proportion of the FSH variance than the total variance explained by the two previously reported FSHR missense variants (rs2300441 R 2 = 1.40% vs rs6166 R 2 = 0.17%, rs6165 R 2 = 0.03%). GWAS for LH did not identify any genome‐wide significant associations. In conclusion, we identified genome‐wide significant association between variants in FSHR and circulating FSH first, with the top associated variant rs2300441 might be a primary contributor at the population level. Abstract :